Reputation: 801
I have been told that the term
(z (λy.z x) (λy.y z))
is already in it's normal form - but I don't understand why. Couldn't one make another beta-reduction in this state and replace all occurences of y
in the term (λy.z x)
by (λy.y z)
, so that it would evaluate to:
(z (λy.z x) (λy.y z)) ==> (z z x)
Upvotes: 3
Views: 96
Reputation:
Application is generally taken to be left-associative. That is,
z (λy.z x) (λy.y z)
is not
z ((λy.z x) (λy.y z))
It is
(z (λy.z x)) (λy.y z)
which would require the value of z
to beta-reduce.
Upvotes: 3